Etude d’une tour RDC + 12 étages avec S.SOL, en béton armé. - Bouklouch, Razika; Ghali, Ouiam (My University, 2024)
يقدم هذا المشروع دراسة تفصيلية لمبنى سكني يتألف من طابق سف لي وطابق أرضي باإلضافة إلى 12 طوابق في والية وهران هذه المنطقة مصنفة في المنطقة الزلزالية حسب القواعد الجزائرية المضادة للزالزل 99 طبعة2003.تم استخدام من اجل الحسابات والتحقق من الخرسانة المسلحة لضمان وتأكيد الدراسة الديناميكية للهيكل استعملنا برنامج من اجل تحديد القوة الناتجة عن مختلف األحمال كالحمل الدائم التشغيل و الحمل الزلزالي أما دعامات المبنى فتتألف من أعمدة مرتبطة يبعضها وجدران من اإلسمنت المسلحة هذه األخيرة بدورها تستعمل في تامين استقرار البناية وتثبيت محيطها، أما أساسات البناية فتم اختيارها لتتحمل الحموالت والقوى المطبقة عليها وتوزعها بشكل منظم على األرض الكلمات المفتاحية: البناية ، خرسانة مسلحة IIa RPA99V2003 ,BAEL9199 ROBOT ROBOT;RPA99 version 2003;BAEL91/99 Summary This work presents a detailed study of a residential building consisting of a basement and a ground floor plus (12) floors, located in the Wilaya of Oran, This region is classified in seismic zone IIa, according to the Algerian earthquake resistant regulations RPA99version 2003. For the calculations and the verifications of the reinforced concrete the modified RPA99V2003 and BAEL9199) were used and to insure and validate the dynamic study of the structure we used the ROBOT software, in order to determine the different loads due to loads (died load, live load and seismic load). The porticoes that associated with the reinforced concrete shear-walls provide the wind-bracing. The peripheral Shear-walls insured the anchoring of the building and the foundation raft adopted to support the loads and to distribute them on the soil Keywords: Building, Reinforced concrete, Robot2023, RPA99version2003, BAEL91/99.
Keywords: Bâtiment; béton armé; Robot2023; RPA99version2003; BAEL91 /99